All Days 2009
DOI: 10.2118/125302-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multilateral Drilling Technology in Increasing Productivity in the Middle East Fields

Abstract: Multilateral drilling (ML) drilling technology is one of the unconventional drilling methods to increase the productivity of a well. It is thought that ML wells could be more economic with higher productivities than other types of wells such as vertical, directional, horizontal or extended reach horizontal wells. Advances in ML drilling has resulted in significant cost saving, greater flexibility and increased profit potential. In the last two decades, thousands of ML wells have been drilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In drilling operations, nanoparticles have been employed to improve the efficiency of the drilling bit [13], optimise the rheological properties [14,15], improve the thermal conductivity of the drilling fluids [16,17], inhibit the shale swelling, friction reduction [18], and reduction of fluid filtration and mudcake thickness [19,20]. However, nanoparticles have been employed in most of the cases improving the rheological and filtration properties in bentonite-based drilling fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In drilling operations, nanoparticles have been employed to improve the efficiency of the drilling bit [13], optimise the rheological properties [14,15], improve the thermal conductivity of the drilling fluids [16,17], inhibit the shale swelling, friction reduction [18], and reduction of fluid filtration and mudcake thickness [19,20]. However, nanoparticles have been employed in most of the cases improving the rheological and filtration properties in bentonite-based drilling fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al concluded that nanoclay and nanosilica stabilize invert emulsion drilling fluids for HTHP applications and observed that they can alter rheology of drilling fluid . Paiaman and Al‐anazi concluded that the addition of nano‐carbon black particles into the drilling fluid decreased the mud cake thickness at HTHP environments, therefore helping prevent stuck pipe problems . Contreras et al concluded that iron‐based and calcium‐based nanoparticles in oil‐based drilling fluids can plug porous media in HTHP conditions and reduce filtration at LPLT conditions.…”
Section: Introductionmentioning
confidence: 99%